Shared History, disputed memory: La Ripa and Moret as bulwarks of a compared identity between Navarra and Aragón - López Calvo, Victor Manuel (Huarte de San Juan. Geografía e Historia, 2021)
Collective identity has been one of the most complex matters concerning the study of a territory’s relationships both between and within itself. In the Iberian Peninsula this complexity only amplifies as, throughout the modern age, constructions of identity inherited from the medieval kingdoms have coexisted with the process of homogenization. In this context, throughout the XVII century a series of historiographic controversies came to the fore between the Navarran and Aragonese communities who were eager to claim their place in the super structure then in formation by brandishing their past as the principle argument. The Jesuit father, José Moret and the Benedictine fray Domingo La Ripa, would become the protagonist of a confrontation that sustained some of the first battles at the beginning of that century and that later, between 1665 and 1685 would be resumed at a time in which the monarchy was adopting a different course that would lead towards the end of an era.
Keywords: Identity; precedence; controversial; Sobrarbe; Aragón